Competition and Facilitation Influence Central Place Foraging Ecology in a Colonial Marine Predator - Liam P. Langley; Sam L. Cox; Samantha C. Patrick; Stephen C. Votier (Ecology and Evolution)
ABSTRACT Coloniality is strongly shaped by aspects of social foraging behaviour. For example, colonies may be important sources of information, while food competition may increase foraging efforts and limit colony size. Understanding foraging ecology considering these apparent trade‐offs is required to develop a better understanding of colonial living. We combined animal‐borne GPS, cameras and dive recorders to study social foraging in breeding adult northern gannets Morus bassanus—a wide‐ranging colonial seabird. We first tested for indirect evidence of prey depletion around the colony by estimating dive location, depth and duration. Next, we tested for sociality during different behaviours (commuting, foraging and resting) and distance from the colony. Finally, we quantified flocks of inbound and outbound birds to compare social foraging between outbound and inbound legs of the commute. Dive probability and depth (n = 46 individuals; n = 1590 dives) increased with distance from the colony, creating dive clusters at ~100 and 180 km consistent with conspecific prey depletion. Camera stills (n = 8 individuals; n = 7495 images) show gannets are highly social, but this varied among behaviours. Sociality was highest during foraging and commuting; especially inbound and social foraging was more likely far from the colony. Gannets were equally likely to be solitary or social when leaving the colony but returning birds were more likely in larger flocks. In summary, despite experiencing intraspecific competition for food, gannets engage in dynamic, context‐dependent social foraging associations. Conspecifics aggregated far from the colony possibly because of a prey depletion halo closer to home, but this provided potential benefits via local enhancement and by returning to the colony in flocks. Our results therefore illustrate how competition may, paradoxically, facilitate some aspects of group foraging in colonial animals.